The Effect of Using Think-Pair-Share Technique on Reading Comprehension of Grade eight Students at SMP Negeri 1 Jorlang Hataran in Narrative Text - Laurensia Manurung; Asima Rohana Sinaga; Irene Adryani Nababan (Departement of Mathematics Education, 2023)
The research was carried out with quantitative research and quasi-experimental design. This research involved students from SMP Negeri 1 Jorlang Hataran. The sample was 60 students, 30 students from VIII-3 as experimental group, while 30 students from VIII-4 as control group. The classes were selected through purposive sampling. Think Pair Share teaching was employed as independent variable (y), with the dependent variable (x) purportedly resulting from it. Researcher gathered data by conducted pre-test, treatment, and post test. Mean of post test for experimental was 87,11, while control group’s was 47,11. The experimental group had post-test standard deviation of 9,41, while control group’s was 12, 62. The mean differences had standard error of 6.73 using significance level of 5%. It was determined that T-test value (5,94) exceeded T-table value (1,672). Thereby, Ho was rejected, whereas Ha was accepted. Hence, Think-Pair-Share had significant efect on students’ reading comprehension.